2010
DOI: 10.1021/jf101982v
|View full text |Cite
|
Sign up to set email alerts
|

Monascin and Ankaflavin Act as Novel Hypolipidemic and High-Density Lipoprotein Cholesterol-Raising Agents in Red Mold Dioscorea

Abstract: Monascus-fermented red mold dioscorea (RMD) has been proven to possess greater hypolipidemic effect than red mold rice (RMR) even though they include equal levels of cholesterol-lowering agent monacolin K. However, higher concentrations of yellow pigments (monascin and ankaflavin) were found in RMD than in RMR. In this study, purified monascin and ankaflavin were administered to hyperlipidemic hamsters for 8 weeks, respectively, to test whether these two compounds were novel hypolipidemic ingredients. In the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 20 publications
1
79
0
Order By: Relevance
“…Lovastatin is recognized as the active component of cholesterol depression in traditional red yeast rice, and high lovastatin content of red yeast rice (0.1 g/kg in Korean and 1 g/kg in China) has already been sold as functional food additive (Jeong 2014). Interestingly, yellow Monascus pigments (monascin and ankaflavin) act as novel hypolipidemic, and high-density lipoprotein cholesterolraising agents are also validated (Lee et al 2010). The yellow Monascus pigment ankaflavin shows selective cytotoxicity to cancer cell lines by an apoptosis-related mechanism while relatively low toxicity to normal fibroblasts.…”
Section: Introductionmentioning
confidence: 98%
“…Lovastatin is recognized as the active component of cholesterol depression in traditional red yeast rice, and high lovastatin content of red yeast rice (0.1 g/kg in Korean and 1 g/kg in China) has already been sold as functional food additive (Jeong 2014). Interestingly, yellow Monascus pigments (monascin and ankaflavin) act as novel hypolipidemic, and high-density lipoprotein cholesterolraising agents are also validated (Lee et al 2010). The yellow Monascus pigment ankaflavin shows selective cytotoxicity to cancer cell lines by an apoptosis-related mechanism while relatively low toxicity to normal fibroblasts.…”
Section: Introductionmentioning
confidence: 98%
“…It is also an anti-inflammatory agent that inhibits the 12-Otetradecanoylphorbol 13-acetate-induced inflammatory response in mice (Akihisa et al 2005). In previous studies, we showed that the RMD may have hypolipidemic and hypoglycemic effects via its secondary metabolite MS (Lee et al 2010b;Shi and Pan 2010a). Chronic inflammation in muscle tissue is linked with type 2 diabetes, insulin resistance, and diabetic complications.…”
Section: Monascin (Ms)mentioning
confidence: 94%
“…In addition, Monascus-fermented products were able to significantly inhibit atherosclerotic plaque formation in the heart aorta of highcholesterol diet-induced hamsters (Fig. 4) (Lee et al 2010). …”
Section: Effects Of Monascus-fermented Products On the Inhibition Of mentioning
confidence: 96%